Topical silicone gel mistaken for a retained orbital foreign body on MRI. Issue 3 (7th March 2022) - Samia-Aly, Emma; Mellington, Faye
Abstract : MRI is now a well-regarded imaging technique, but due to its use of strong magnetic fields, some metallic objects are contraindicated. We present a case of a man in his 40s with thyroid eye disease, who underwent bilateral orbital decompression. Following surgery, he was advised to start scar massage with topical silicone gel (Dermatix). He later underwent an MRI head scan which was halted due to concerns of a retained metallic foreign body. Topical silicone gel is widely used clinically for scar management. Due to its properties, it can cause the appearance of an artefact on MRI and be mistaken for a metallic foreign body. We present the first case to our knowledge of an MRI susceptibility artefact which was attributed to topical silicone gel and describe the diagnostic confusion it caused. We recommend asking patients to wash off any topical silicone gel before having an MRI scan.